Zoltan Kodály and Stanislav Lyudkevych - Chekan, Yurii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
There is a fairly rich base for comparing Kodály (1882–1967) and Lyudkevych (1879–1979). Both musicians were from one generation, shared their social background and received the same education. They had the same areas of their professional implementation. Both musicians represent ancient musical cultures that were freed from imperial influence in the early 20th century. If Hungarian culture got rid of the German influence, then Ukrainian culture fell under Soviet pressure, remaining colonial. This explains mainly the difference in the methods and results of the implementation of folk, composer, pedagogical work of Kodály and Lyudkevych.